The Impact of the Use of Environmentally Friendly Raw Materials and Green Marketing Communication on Corporate Reputation and Profitability in the Manufacturing Industry in Central Java - Rina Juwita; Rizaldy Rizaldy; Tirta Yoga (Westscience Press, 2024)
This study examines the impact of environmentally friendly raw materials and green marketing communication on corporate reputation and profitability within the manufacturing industry in Central Java. Utilizing a quantitative research approach, data were collected from 140 manufacturing firms, analyzed using a Likert scale ranging from 1 to 5. The data were processed with Structural Equation Modeling-Partial Least Squares (SEM-PLS 3) to evaluate the proposed hypotheses. The findings reveal that both the use of environmentally friendly raw materials and green marketing communication have positive and significant effects on corporate reputation and profitability. These results highlight the strategic importance of sustainability practices in enhancing corporate outcomes. The study underscores the value of integrating environmentally conscious operations and effective communication strategies to achieve competitive advantages in the manufacturing sector. By adopting sustainable practices and promoting these efforts through targeted marketing communications, companies can strengthen their market position and financial performance.